Hubungan Pengetahuan dan Sikap dengan Stunting pada Balita di Puskesmas Setu 1 - Farida Mariani; Asep Barkah (Universitas Malahayati Lampung, 2024)
ABSTRACT Stunting or what is commonly referred to as stunting under five is one of the main nutritional problems suffered by infants in Indonesia. Around 150.8 million or 22.2% in 2017 toddlers suffer from stunting in the world. Information on the prevalence of stunting in children under five compiled by WHO (World Health Organization) shows that in the Southeast Asian region, Indonesia is ranked third with the highest prevalence. The prevalence of stunting among toddlers in 2005-2017 in Indonesia averaged 36.4%. Based on distribution points, almost all provinces except South Sumatra and Bali, have stunting percentages above the WHO limit. The provinces with the highest stunting were West Sulawesi (39.7) and East Nusa Tenggara (38.7). Based on West Java Profile data for 2021, the prevalence of short toddlers based on the height-for-age index (TB/U) in 2021 is 6.08%. Health Profile of Bekasi Regency for 2020, based on the Anthropometric Index, namely height for age (PB/U or TB/U), there are 4.2% of toddlers with stunting status. Factors that influence the incidence of stunting in toddlers are knowledge, attitude. Analyzing the relationship between knowledge and attitudes with stunting in toddlers at the Setu 1 Health Center. Analytical with cross sectional approach. The sample in this study were all mothers with toddlers aged 0-60 months who were treated at the Setu 1 Health Center on 01-30 May 2023 when the questionnaire was distributed to 51 people. The sampling technique uses accidental sampling. There are toddlers who experience stunting 3.9%. Respondents with good knowledge were 58.8% and respondents who had a positive attitude were 70.6%. There is a relationship between knowledge and the incidence of stunting in toddlers, the results of the Chi-Square statistical test obtained a value of p.value.0.004. And there is a relationship between attitude and stunting in toddlers, the results of the Chi-Square statistical test obtained a p.value of 0.25. There is a relationship between knowledge, attitudes and stunting in toddlers. Health workers are expected to be more active in providing education about stunting to the public so that the incidence of stunting in toddlers is reduced. Keywords: Knowledge, Attitude, Stunting, Toddlers ABSTRAK Stunting atau yang biasa disebut dengan peristiwa balita pendek adalah salah satu permasalahan gizi utama yang diderita oleh bayi di Indonesia. Sekitar 150,8 juta atau sebesar 22,2% pada tahun 2017 balita menderita stunting di dunia. Informasi mengenai prevalensi pada balita yang mengalami stunting yang dihimpun WHO (World Health Organization) menampilkan bahwa di regional Asia Tenggara, Indonesia berada pada peringkat ketiga dengan prevalensi paling tinggi. Prevalensi pada balita stunting tahun 2005- 2017 di Indonesia rata-rata sebesar 36,4%. Berdasarkan titik sebaran, hampir seluruh provinsi kecuali Sumatera Selatan dan Bali, memiliki persentase stunting di atas batas WHO. Adapun provinsi dengan stunting tertinggi adalah Sulawesi Barat (39,7) dan Nusa Tenggara Timur (38,7). Berdasarkan data Profil Jawa Barat tahun 2021, Prevalensi balita pendek berdasarkan indeks tinggi badan per umur (TB/U) tahun 2021 sebesar 6,08 %. Profil Kesehatan Kabupaten Bekasi Tahun 2020, berdasarkan Indeks Antropometri yaitu tinggi badan menurut umur (PB/U atau TB/U), terdapat 4,2 % balita dengan status stunting. Faktor yang mempengaruhi kejadian Stunting pada balita adalah pengetahuan, sikap. Menganalisis hubungan. Analitik dengan pendekatan cross sectional. Sampel dalam penelitian ini adalah seluruh ibu yang memiliki Balita usia 0-60 bulan yang berobat di Puskesmas Setu 1 pada tanggal 01 – 30 Mei 2023 pada saat penyebaran kuesioner sebanyak 51 orang. Teknik pengambilan sampel menggunakan accidental sampling. Terdapat balita yang mengalami Stunting 3,9%. Responden berpengetahuan baik 58,8% dan responden yang memiliki sikap positif 70,6%. Adanya hubungan antara pengetahuan dengan kejadian Stunting pada balita, hasil uji statistic Chi-Square diperoleh nilai p.value.0,004. Dan adanya hubungan antara sikap dengan kejadian Stuntung pada balita, hasil uji statistic Chi-Square diperoleh nilai p.value 0,25. Adanya hubungan antara pengetahuan, sikap dengan kejadian Stunting pada balita. Tenaga kesehatan diharapkan lebih aktif lagi dalam memberikan edukasi tentang Stunting kepada masyarakat supaya kejadian Stunting pada balita berkurang. Kata Kunci: Pengetahuan, Sikap, Stunting, Balita